Sensitive and selective detection of mercury ions based on papain and 2, 6-pyridinedicarboxylic acid functionalized gold nanoparticles. Issue 4 (4th January 2016) - Lai, Cui; Qin, Lei; Zeng, Guangming; Liu, Yunguo; Huang, Danlian; Zhang, Chen; Xu, Piao; Cheng, Min; Qin, Xiangbin; Wang, Manman
Abstract : Here we demonstrate the rational design of a sensitive and selective colorimetric method for mercury ion (Hg 2+ ) detection by using papain and 2, 6-pyridinedicarboxylic acid (PDCA) functionalized gold nanoparticles (AuNPs). Abstract : Here we demonstrate the rational design of a sensitive and selective colorimetric method for mercury ion (Hg 2+ ) detection by using papain and 2, 6-pyridinedicarboxylic acid (PDCA) functionalized gold nanoparticles (AuNPs). Papain is a protein with seven cysteine residues and 212 amino acid residues, which can combine with Hg 2+, and PDCA is a chelating ligand, which has a strong affinity for Hg 2+ . Selectivity measurements reveal that the sensor is specific for Hg 2+ even with interference by high concentrations of other metal ions. This sensor was also used to detect Hg 2+ ions from real samples of tap water, river water, and pond water spiked with Hg 2+ ions, and the results showed good agreement with the found values determined by atomic fluorescence spectrometry. The absorbance ratio ( A 650 / A 520 ) was linear with the Hg 2+ concentration in the range of 0.01 μM to 14 μM. Under the optimum conditions (1.0 × 10 −7 M papain, 5.0 × 10 −4 M PDCA, pH 6.0 at 30 °C), the detection limit of Hg 2+ was as low as 9 nM, which met the maximum allowable standard of the Environmental Protection Agency (EPA) set in drinking water. In conclusion, the P-PDCA-AuNPs sensor can be used to detect the concentration of Hg 2+ with high sensitivity and good selectivity, and it can lead to dramatically improved colorimetric sensors.